PRe-hospital Evaluation of Sensitive TrOponin (PRESTO) Study: multicentre prospective diagnostic accuracy study protocol - Richard Body; Aloysius Siriwardena; Abdulrhman Alghamdi; Edward Carlton; Kim Kirby; Mark Hann; Eloïse Cook; Alexander Thompson; Angela Foulkes; John Phillips; Jamie Cooper; Steve Bell; et al. (BMJ Open)
Introduction Within the UK, chest pain is one of the most common reasons for emergency (999) ambulance calls and the most common reason for emergency hospital admission. Diagnosing acute coronary syndromes (ACS) in a patient with chest pain in the prehospital setting by a paramedic is challenging. The Troponin-only Manchester Acute Coronary Syndromes (T-MACS) decision rule is a validated tool used in the emergency department (ED) to stratify patients with suspected ACS following a single blood test.We are seeking to evaluate the diagnostic accuracy of the T-MACS decision aid algorithm to ‘rule out’ ACS when used in the prehospital environment with point-of-care troponin assays. If successful, this could allow paramedics to immediately rule out ACS for patients in the ‘very low risk’ group and avoid the need for transport to the ED, while also risk stratifying other patients using a single blood sample taken in the prehospital setting.Methods and analysis We will recruit patients who call emergency (999) ambulance services where the responding paramedic suspects cardiac chest pain. The data required to apply T-MACS will be prospectively recorded by paramedics who are responding to each patient. Paramedics will be required to draw a venous blood sample at the time of arrival to the patient. Blood samples will later be tested in batches for cardiac troponin, using commercially available troponin assays. The primary outcome will be a diagnosis of acute myocardial infarction, established at the time of initial hospital admission. The secondary outcomes will include any major adverse cardiac events within 30 days of enrolment.Ethics and dissemination The study obtained approval from the National Research Ethics Service (reference: 18/ES/0101) and the Health Research Authority. We will publish our findings in a high impact general medical journal.Trial registration number Registration number: ClinicalTrials.gov, study ID: NCT03561051